Investigation of life cycle cost (LCC) analysis practice of university mosque maintenance during the in use phases - Abuznaid, Salem M.A (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Mosque is a remarkable place for Muslims, where Muslims perform 5 prayers and worship Allah every day. The maintenance of the mosque during the in use phases need to be accomplished effectively with sufficient budgetary planning. Mosque maintenance during the in use phases is essential to extend mosque life cycle. However, mosque maintenance during the in use phases is being actualized ineptly in an aimless path and without adequate economical system to identify maintenance cost. Life cycle cost LCC is a procedure that can be applied to quantify and evaluate the economic performance of mosque during the in use phases over it is life cycle. The aim of this research is to investigate LCC practice of university mosque maintenance during the in use phases (operation phases, maintenance phases, and selvage phases) of Mahallah Ruqayyah Mosque (MUSOLLA AR-RAHMAN). The research seeks to achieve the following objectives; (i). to review the practice of LCC of university mosque maintenance during the in use phases of MUSOLLA AR-RAHMAN (, (ii). to identify the required data that can be used as inputs for LCC practice of university mosque maintenance during the in use phases of MUSOLLA AR-RAHMAN, (iii). to identify the appropriate strategies that can be used to enhance LCC practice of university mosque maintenance during the in use phases of MUSOLLA AR-RAHMAN. The methodology utilized involves literature review, interview questionnaire and case study. Previous studies in related to this area have shown there is limited practice of LCC of university mosque maintenance during the in use phases. In addition, the literature study has identified the main types of data that can be used as inputs of LCC practice of university mosque maintenance during the in use phases. The findings of the interview questionnaire demonstrate that all respondents share the same opinion and judgment that there is limited practice of LCC of mosque maintenance during the in use phases. Furthermore, the interview questionnaire has established unanimity in related to the types of data that can be used as inputs of LCC practice of university mosque maintenance during the in use phases. The case study has found the main facilities that used in the university mosque, and the appropriate maintenance types that can be used to maintain university mosque facilities. In addition, the case study shows the main types of data that can be used in LCC practice of university mosque maintenance during the in use phases. Based on the outcomes of data collected by primary approaches (interview questionnaire and case study) and secondary approach (literature review) many appropriate strategies have been found; which can be applied to enhance the practice LCC of university mosque maintenance during the in use phases, among the appropriate strategies 3 strategies have been highlighted with higher mean score, which are; construct a database to save the historical data of maintenance works, establish a training program to improve the skills of maintenance technician, and establish a system to write and to save the annual reports.